Penelitian jumlah penggunaan bating agent pada penyamakan kulit sarung tangan (fashion glove) dari kulit kelinci - Lutfi, Muchtar; Widhiati, Widhiati; Rahayu, Esti; Nainggolan, Kasmin (Majalah Kulit, Karet, dan Plastik, 1994)
The objective of this research is to identify the quatity of bating agent used in tanning rabbit skins to be glove leather, to make use rabbit skins which can not be tanned to fur rabbit skin leather. The materials used in this research were of 40 pieces of lokal salt preservated rabbit skins originated from Yogyakarta having quality III and IV. They were grouped into four and the groups consisted of ten pieces each were tanned to be fashion glove leather using 4% formaline as pretanning agent and followed by chrome tanning agent as the retanning agent. Before carrying out both tanning processes bating was done on them using Pancreol Bate as bating agent. The quantity of bating agent added was varried as 0,65%, 1,2%, 1,8% and 2,4%. The process used was of usually carried - out by IRDLAI. The leather produced were tested on their sotfness, with sheepskin glove leather was used as the measuring- rod; their tensile strength resistance and flexibility with SII. 0061 â 74 (Quality and test method for goatsheep skin glove and garment leather) as the standard of comparison. The test results were statistically evaluated. A conclusion can be down from this research that by using 0,6% Pancreol Bate on bating process, soft glove leathers having good tensile strength and flexibility which fulfill the requirements of SII. 0061 - 74 can be produced.